Efficacy of hip strengthening on varus thrust in knee osteoarthritis - Mohamed, Heba E; Youssef, Enas F; Rezk, Abd-Elrahman A; Mohamedy, Eslam A; Elmelhat, Ahmed M; Mohamed, Nabil A (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The objective of this study was to investigate the effect of hip strengthening exercises on varus thrust in patients with knee osteoarthritis (OA). A double-blind clinical experimental study was carried out. Eighty-eight of the ninety-three eligible subjects participated. Participants were between 45 to 60 years of age, had a body mass index (BMI) of < 30 kg/m², and medial tibiofemoral OA with a radiographic grade of 2-3 according to Kellgren-Lawrence (KL). Participants were randomly allocated to one of the two groups (control and study group). The control group (n=44; 22 men, 22 women) received only quadriceps strengthening exercise, and stretching exercise for hamstring and calf muscles, while the study group (n=44; 22 men, 22 women) received hip abductor, hip extensor, hip external rotator strengthening exercises in addition to the same exercises of the control group. Patients in both groups received 12 sessions of treatment (3 sessions per week for 4 weeks). The primary outcome was frontal plane projection angle (FPPA), which was measured by a digital video camera and analysed with Kinovea software. Secondary outcomes were muscles strength of hip abductor, hip extensor, hip external rotator and quadriceps measured with a handheld dynamometer (HHD). At baseline, there was no statistically significant difference between both groups regarding tested variables (p > 0.05). After 4 weeks of treatment, both groups showed statistically significant improvements in FPPA, hip abductors, hip extensors, hip external rotators and knee extensor strength, compared to pre-treatment (p < 0.05). However, the study group showed statistically significant improvements in FPPA, hip abductors, hip extensors, and hip external rotators strength compared with the control group (p < 0.05), while there was no statistically significant difference in knee extensor strength between both groups (p > 0.05). Hip strengthening exercises can be added to the treatment programme of varus thrust.